The complexity of nitric oxide generation and function in plants - Benavides, Maria Patricia (2016)
Plants are exposed to environmental stress, in natural and agricultural conditions.Nitric oxide (NO), a small gaseous molecule which plays important roles in plants, has been involved in many physiological processes, and emerged as an important endogenous signaling molecule in the adaptation of plants to biotic and abiotic stress. NO is produced from a variety of enzymatic and non enzymatic sources, which are not yet fully understood. Also, NO and reactive nitrogen species (RNS) can produce posttranslational modifications affecting protein function. Nitrate reductase, a key enzyme in the nitrogen metabolism, is a proposed source of NO in plants which could be affected by posttranslational modifications.Thus, different pathways seem to be involved and can also regulate NO synthesis in the plant cell under physiological or stress conditions. However, how the levels of NO are reached in such time and place to fulfill its functions, are still puzzles to elucidate.